Study of Length of Time to Reach Heat Unit due to Various Volumes and Frequencies of Watering in Garlic Plant (Allium sativum L.) - Amin, Bahrul Mubin; Suminarti, Nur Edy (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2022)
Garlic is one of the important horticultural commodities in Indonesia which is widely used its tubers as a cooking and medicinal ingredient. The large number of land conversion activities and competition between horticultural crops in the highlands have led to the development of garlic plants directed to lower land with different environmental conditions. The aim of this research is to study the volume and frequency of watering to length of time to reach heat unit of garlic. The research was carried out in February-May 2020 at the Greenhouse of the Faculty of Agriculture, Brawijaya University in Jatimulyo, Lowokwaru, Malang. The tools used are polybags, hoe, measuring cup, knife, tape measure, leaf area meter, camera, treatment board, stationery, lux meter, alcohol thermometer and thermohigrometer. The materials used are Lumbuh Putih variety, soil, and NPK fertilizer. This research was compiled with Split Plot Design with volume of watering as a main plot: J1: 400 mm / season, J2: 600 mm / season, J3: 800 mm / season, and J4: 1000 mm / season, while the frequency watering as a sub-plot: P1: watering once a day, P2: watering once every 2 days, and P3: watering once every 3 days. Total combination of treatments from the two factors was 12 treatments, each treatment repeated 3 times, so there were 36 experimental plots. Each experimental plot consist of 15 plants so there were 540 plants in total. Data observations were analyzed using the F test. If there is an interaction or effect of the treatment, a further test is carried out using the HSD test at 5% level. The results of J4 and P1 treatments required a longer time to reach the heat unit for each phase of garlic plant growth.